Islamic Activism, Local Politics, and Contradiction of Democratisation in North Sumatra - Riza, Faisal; Junaidi, Junaidi (Politeia: Jurnal Ilmu Politik, 2019)
This paper focus on examining the transformation of Islamic activism in North Sumatra especially their movement, which was echoed by the Aksi Bela Islam in Jakarta 2016, in this region in post- punishment of Basuki Tjahaja Purnama between 2017 and 2018. The study analyses their movement in keeping the narration of politics, discourse of intimidated Islam, and then all these have been capitalised for political interest in regional election such as governor election in North Sumatra 2018. The study is approached by social movement theory, Islamic social movement, and then being related to the project of democratization and the contemporary narration of Indonesia nationalism. This study argues that firstly, this movement is still going on move longer than many scholar predicted because their ability to keep discourse and analize political structure opportunity. Secondly, fragmentation in the body of movement can not be avoided because working disorientation and their relation with political elit and electoral politics. Third, the shadow of this movement existence remains a big challenge for democratization project in North Sumatra and generally Indonesia.